Peran Pendidik Dalam Membimbing Peserta Didik Dyscalculia Pada Siswa Kelas III SD Muhammadiyah 16 Surakarta Tahun Pelajaran 2015/2016 - Normalita, Pramula; , Drs. Saring Marsudi, SH. M.Pd; , Drs. Suwarno, SH., M.Pd (2015)
This study aimed to describe: 1) The characteristics of students who have difficulty learning mathematics (dyscalculia). 2) The role of teachers in guiding students who have difficulty learning mathematics (dyscalculia). 3) How educators guide students who have difficulty learning mathematics (dyscalculia). 4) difficulty in guiding teachers who have difficulty learning mathematics (dyscalculia). 5) Solution educators to cope with students who have difficulty learning mathematics (dyscalculia). This type of research is qualitative research (Qualitative Research). The informants are third grade teacher. Data collection techniques used were observation, interviews, documentation. Data was analyzed through the steps of data reduction, data presentation and conclusion. Mechanical data validity checking is done by triangulation. These results indicate that the SD Muhammadiyah Surakarta 16've done guidance on learners who have dyscalculia. Although there is little resistance but the teachers have been providing solutions that these obstacles can be minimized. Keywords: Role of Educators, Dyscalculia, Dyscalculia Solutions